Signaling Molecule Hydrogen Sulfide Improves Seed Germination and Seedling Growth of Maize (Zea mays L.) Under High Temperature by Inducing Antioxidant System and Osmolyte Biosynthesis - Zhou, Zhi-Hao; Wang, Yue; Ye, Xin-Yu; Li, Zhong-Guang (Frontiers in Plant Science, 2018)
Hydrogen sulfide (H2S) is a novel type signaling molecule in plants. Seed germination is a key stage of life cycle of plants, which is vulnerable to environmental stress including high temperature. However, under high temperature stress, whether pre-soaking of maize seeds with NaHS (a H2S donor) could improve seed germination and seedling growth and the possible mechanisms are not completely clear. In this study, maize seeds pre-soaked with NaHS enhanced germination percentage, sprout length, root length, and fresh weight compared with the control without NaHS treatment, illustrating that H2S could improve maize seed germination and seedling growth under high temperature. In addition, in comparison to the control, NaHS pre-soaking stimulated antioxidant enzymes (ascorbate peroxidase, glutathione reductase, guaiacol peroxidase, superoxide dismutase, and catalase) activities and the contents of water soluble non-enzymatic antioxidants (ascorbic acid and glutathione), as well as the ratio of reduced antioxidant to oxidized antioxidant. Moreover, pre-soaking with NaHS activated 1-pyrroline-5-carboxylate synthetase and ornithine aminotransferase (both are rate-limiting enzymes in proline synthesis), betaine aldehyde dehydrogenase (a key enzyme in glycine betaine), and trehalose-6-phosphate phosphatase (a key step in trehalose synthesis), which in turn accumulated proline, glycine betaine, and trehalose in germinating seeds compared with the control. Also, an improved germination by NaHS under high temperature was reinforced by the above osmotic adjustment substances (osmolytes) alone, while deteriorated by the inhibitors of osmolyte biosynthesis (gabaculine, disulﬁram, and sodium citrate). These results imply that H2S could improve maize seed germination and seedling growth under high temperature by inducing antioxidant system and osmolyte biosynthesis.